2012
DOI: 10.1161/circresaha.111.261933
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Costimulatory Receptors OX40 and 4-1BB Characterize CD4 + CD28 null T Cells in Patients With Acute Coronary Syndrome

Abstract: Rationale:Patients with acute coronary syndrome (ACS) predisposed to recurrent coronary events have an expansion of a distinctive T-cell subset, the CD4 ؉ CD28 null T cells. These cells are highly inflammatory and cytotoxic in spite of lacking the costimulatory receptor CD28, which is crucial for optimal T cell function. The mechanisms that govern CD4 ؉ CD28null T cell function are unknown.Objective: Our aim was to investigate the expression and role of alternative costimulatory receptors in CD4 ؉ CD28 null T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 46 publications
2
111
0
1
Order By: Relevance
“…A proatherogenic effect has been demonstrated for CD80, CD86, and CD252 (136,137,139) as well as for CD137, a costimulatory receptor expressed on T lymphocytes (138,140). Human CD4 + CD28 null T cells, which are associated with ACS, express high levels of the costimulatory receptors CD134 and CD137 compared with conventional CD4 + CD28 + T cells, and in vitro studies show that the ligands for these receptors can costimulate these T cells (141).…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…A proatherogenic effect has been demonstrated for CD80, CD86, and CD252 (136,137,139) as well as for CD137, a costimulatory receptor expressed on T lymphocytes (138,140). Human CD4 + CD28 null T cells, which are associated with ACS, express high levels of the costimulatory receptors CD134 and CD137 compared with conventional CD4 + CD28 + T cells, and in vitro studies show that the ligands for these receptors can costimulate these T cells (141).…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsesmentioning
confidence: 99%
“…Blocking Abs specific for CTLA-4 or PD-1 are both being used to enhance T cell-mediated antitumor responses in cancer patients (153). Therapeutic blockade of TNF/TNFR superfamily members such as the OX40 ligand/OX40 pathway may be effective for inhibiting CD4 + CD28 -T cells in the setting of ACS (141). In addition, B cell-depletion strategies are being investigated as well, and their impact on B-2 and B-1 cells and on CVD needs to be determined.…”
Section: Translational Aspects Of New Understandingsmentioning
confidence: 99%
“…Moreover, CD28– T cells were shown to produce the cytotoxic molecules perforin and granzyme B, which resulted in cytolysis of the endothelium in vitro 29, 30. CD4+CD28– T cells have been found in patients with cerebrovascular and cardiovascular diseases such as acute coronary syndrome27, 31 and stroke 32, 33, 34. Of note, in these patients this proinflammatory cytokine production is upregulated by the costimulatory receptors OX40 and CD137 on circulating CD4+CD28– T cells,25 which were also found to be located in atherosclerotic plaques preferentially accumulating in unstable lesions 35.…”
Section: Discussionmentioning
confidence: 99%
“…In the CD137‐deficient atherosclerotic vessels of ApoE − / − CD137 − / − mice, crosslinking CD137L activation with soluble CD137 protein ex vivo activated CD137L signaling and led to the release of proinflammatory cytokines, such as TNF‐α and monocyte chemotactic protein‐1 (MCP‐1) 11. In ACS patients, blocking the CD137 pathway in vitro remarkably reduced the production of TNF‐α and IFN‐γ from circulating CD4+CD28– T cells, which were reported to induce rupture of atherosclerotic plaques by direct cytolysis of arterial smooth muscle and endothelial cells 27, 30. In our serial study, despite an irregular change of lymphocyte counts in the stroke patients, CD137 expression in the CD4+ and CD4+CD28– T cells displayed a decreasing trend at 3 and 14 days posttreatment with statin, a well‐known cholesterol‐lowering drug with multiple antiinflammatory properties 36.…”
Section: Discussionmentioning
confidence: 99%
“…The Atorvastatin for Reduction of Myocardial Damage during Angioplasty (ARMYDA) trial demonstrated that intensive atorvastatin could reduce PMI in patients undergoing PCI, and it is hypothesized that the favorable clinical prognosis associated with intensive statin therapy results from an anti-inflammatory effect mediated by these agents [2][3][4]. Plaque rupture can occur following PCI, and may induce both a local and systemic inflammatory response that is accompanied by the release of inflammatory factors for leukocyte and platelet activation (e.g., TNF-α, IL-6) [5][6][7]. Phosphatase and tension homolog deleted on chromosome ten (PTEN) has been identified as a tumor-suppressor gene and has been associated with maintaining the balance between cell survival and cell death, and which has been shown to inhibit an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%